Identification of the Tolfenamic Acid Binding Pocket in PrbP from Liberibacter asiaticus - Pan, Lei; Gardner, Christopher L.; Pagliai, Fernando A.; Gonzalez, Claudio F.; Lorca, Graciela L. (Frontiers in Microbiology, 2017)
In Liberibacter asiaticus, PrbP is an important transcriptional accessory protein that was found to regulate gene expression through interactions with the RNA polymerase β-subunit and a specific sequence on the promoter region. It was found that inactivation of PrbP, using the inhibitor tolfenamic acid, resulted in a significant decrease in the overall transcriptional activity of L. asiaticus, and the suppression of L. asiaticus infection in HLB symptomatic citrus seedlings. The molecular interactions between PrbP and tolfenamic acid, however, were yet to be elucidated. In this study, we modeled the structure of PrbP and identified a ligand binding pocket, TaP, located at the interface of the predicted RNA polymerase interaction domain (N-terminus) and the DNA binding domain (C-terminus). The molecular interactions of PrbP with tolfenamic acid were predicted using in silico docking. Site-directed mutagenesis of specific amino acids was followed by electrophoresis mobility shift assays and in vitro transcription assays, where residues N107, G109 and E148 were identified as the primary amino acids involved in interactions with tolfenamic acid. These results provide insight into the binding mechanism of PrbP to a small inhibitory molecule, and a starting scaffold for the identification and development of therapeutics targeting PrbP and other homologs in the CarD_CdnL_TRCF family.